Contributions from the systematic review of economic evaluations: the case of childhood hepatitis A vaccination in Brazil Contribuições da revisão sistemática de avaliações econômicas: o exemplo da vacinação infantil contra hepatite A no Brasil - Patrícia Coelho De Soárez; Ana Marli Christovam Sartori; Andreia Santos; Alexander Itria; Hillegonda Maria Dutilh Novaes; Celina Maria Turchi Martelli (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
The aim of this study was to present the contributions of the systematic review of economic evaluations to the development of a national study on childhood hepatitis A vaccination. A literature review was performed in EMBASE, MEDLINE, WOPEC, HealthSTAR, SciELO and LILACS from 1995 to 2010. Most of the studies (8 of 10) showed favorable cost-effectiveness results. Sensitivity analysis indicated that the most important parameters for the results were cost of the vaccine, hepatitis A incidence, and medical costs of the disease. Variability was observed in methodological characteristics and estimates of key variables among the 10 studies reviewed. It is not possible to generalize results or transfer epidemiological estimates of resource utilization and costs associated with hepatitis A to the local context. Systematic review of economic evaluation studies of hepatitis A vaccine demonstrated the need for a national analysis and provided input for the development of a new decision-making model for Brazil. O objetivo deste estudo foi apresentar as contribuições da revisão sistemática de avaliações econômicas para o desenvolvimento de um estudo nacional, o caso da vacinação infantil contra hepatite A. Foi realizada revisão da literatura nas bases de dados EMBASE, MEDLINE, WOPEC, HealthSTAR, SciELO e LILACS, no período de 1995 a 2010. A maioria dos estudos (8 em 10) mostrou resultados favoráveis de custo-efetividade. As análises de sensibilidade indicaram como parâmetros mais importantes para os resultados os custos da vacina, incidência de hepatite A e custos médicos da doença. Foi observada variabilidade nas características metodológicas e estimativas de variáveis-chaves dos 10 estudos revisados. Não é possível generalização dos resultados e transferibilidade de estimativas epidemiológicas, de usos de recursos e custos associados à hepatite A para o contexto local. A revisão sistemática dos estudos de avaliação econômica da vacina contra hepatite A demonstrou a necessidade de uma análise nacional e forneceu elementos para o desenvolvimento de um novo modelo de decisão para o Brasil.